Diagnostic Capability of Next-Generation Sequencing Fusion Analysis in Identifying a Rare CASE of TRAF1-ALK-Associated Anaplastic Large Cell Lymphoma - Agarwal, Indu; Sabatini, Linda; Alikhan, Mir B. (Frontiers in Oncology, 2020)
Background: Anaplastic lymphoma kinase (ALK)-positive anaplastic large cell lymphoma (ALCL) is a rare T-cell neoplasm, accounting for approximately 3% of adult non-Hodgkin lymphomas. Although NPM1 is the most common fusion partner with ALK, many others have been described, necessitating break-apart FISH studies for confirmation of the diagnosis. TNF receptor-associated factor 1 (TRAF1) is a rare ALK partner that is thought to confer a worse prognosis in patients. We describe the utility of next-generation sequencing (NGS) RNA analysis in detection of this uncommon ALK partner.